The Offshoring Phenomenon (2014)
This paper explains some definitions which are necessary in order to understand the offshoring concept, going through the most relevant works about the development of the offshoring phenomenon and its impact on the demand for labor and on the most skilled workers' income -- It is evidenced that the offshoring processes not only deal with the purchase and sale of goods anymore, but that the service sector has an increasingly important role, and that the lower cost is not the only aspect that matters when offshoring, but aspects such as the language and culture are also considered -- It is also found that technology and research related services flow not only from the parent companies towards its subsidiaries, but from firms in less developed countries to other companies in advanced countries -- It concludes with a review of the works that explores the relationship between offshoring, employment and wages, from both, a macro and microeconomic outlook. In the latter case, special consideration is given to the work carried out by Amity and Wei (2006), Crinó (2010), and Geishecker and Görg (2013)